Odpowiedzi

2010-03-28T16:19:51+02:00
A]
2x+y=8
x=3

2×3+y=8
6+y=8
y=8-6
y=2
spr. 2×3+2=8
8=8
b]
3x-2y=6
x=4

3×4-2y=6
12-2y=6
-2y=6-12
-2y=-6
y=-6:-2
y=3
spr.:3×4-2×3=6
12-6=6
6=6
c]
-x-3y=5
y=-2x

-x-3×(-2x)=5
-x+6x=5
5x=5
x=5:5
x=1
y=-2×1=-2
spr. -1-3×(-2)=5
-1+6=5
5=5
e]
3x+y=10
y=2x

3x+2x=10
5x=10
x=10:5
x=2
y=2×2=4
spr. 3×2+4=10
6+4=10
10=10
f]
4x-y=6
y=x

4x-x=6
3x=6
x=6:3
x=2
y=x=2
spr, 4×2-2=6
8-2=6
6=6
2010-03-28T16:21:20+02:00
A)
2x+y=8
x=3

6+y=8
x=3

y=8-6
x=3

y=2
x=3

b)
x-y=6
y=-1

x - (-1)=6
y=-1

x= 6+1
y=-1

x= 7
y=-1

c)
3x-2y=6
x=4

12- 2y =6
x=4

-2y= 6-12
x=4

-2y= -6 / : (-2)
x=4

y= 3
x=4

d)
-x-3y=5
y=-2x

-x= 3y +5 / *(-1)
y=-2x

x= 3y +5
y= 2( 3y +5)

x= 3y+5
y= 6y +10

x= 3y+5
-5y=10/ :(-5)

x= 3y+5
y=-2

y=-2
x=-6 +5

y=-2
x= -1












Najlepsza Odpowiedź!
2010-03-28T16:27:34+02:00